“INVESTIGATION OF THE EFFICIENCY IMPACT OF IRRIGATION REGIMES ON COTTON GROWTH AND DEVELOPMENT” - Ashurova Gulmira Aminovna (TADQIQOTLAR, 2025)
Cotton  does not  consume  the  same  amount of  water at  all stages of growth, setting a specific water and nutrient regime for each phase of its development, taking into  account  the  interaction  between  soil,  water  and  plant  need  Violation  of  the interdependence slows down the growth of the plant, slows its development and delays the passage of the basic phases.